Novel Histone Deacetylase Inhibitors with Enhanced Enzymatic Inhibition Effects and Potent in vitro and in vivo Anti-tumor Activities - Zhang, Lei (2013)
In the present work, a series of small molecules were designed and synthesized based on structural optimization. Significant improvement in the enzymatic inhibition activity of the synthesized compounds was discovered. Moreover, tested compounds have moderate preference for class I HDACs over HDAC6 proved by enzymatic selectivity assay. The in vitro anti-proliferation assay reveals that representative compounds can selectively inhibit the growth of the non-solid lymphomatous cells and leukemic cells such as U937, K562 and HL60 cell lines. In the in vivo anti-tumor assay, molecule D17 showed better performance than SAHA in inhibition of U937 tumor growth. The western blot analysis revealed that representative molecules can block the function of both class I HDACs and HDAC6. More importantly, our western blot results revealed that the levels of some oncogenic proteins (p-Akt in the PI3K/AKT/mTOR signal pathway, c-Raf and p-Erk in the MAPK signal pathway) were dramatically down-regulated by our compounds in U937 cell line rather than MDA-MB-231 cells. This cellular mechanism difference might be an important reason why U937 cell line was more sensitive to our HDACs inhibitors than MDA-MB-231 cell line.